EVALUASI KINERJA STRUKTUR GEDUNG 34 LANTAI DI SURABAYA MENURUT SNI 1726:2012 DAN SNI 1726:2019 - Adi Nugroho Santoso; Made Dharma Astawa (Jurnal Teknik Sipil, 2022)
Indonesia has undergone several earthquake regulations updates, starting from Peraturan Muatan Indonesia 1970 to SNI 1726:2019. This update requires earthquake loads with a larger return period. This has an impact on the existing buildings that were planned to use the old regulations. It is feared that the building does not meet the requirements required by the new regulations, so a review of the performance of the building is needed. This research will use a case study of a Cornell apartment building with 34 floors in the city of Surabaya, which is planned based on SNI 1726:2012 with concrete regulations SNI 2847:2013 and will be evaluated with SNI 1726:2019. The analysis uses Performance Based Design with the Nonlinear Time History Analysis method which was carried out in the 2016 ETABS program. The background to the use of the Performance Based Design method is its use which is quite easy to apply and can also be used to measure the efficiency of the structure being reviewed. The use of Nonlinear Time History Analysis is based on the fact that the use of this method has been regulated in SNI 1726:2019 and the use of this method is considered closest to the actual conditions in the field. Nonlinear Time History analysis in this study uses time history data from the Chichi earthquake in Taiwan in 1999. The evaluation of building performance is based on the performance level refer to FEMA 356. The results of the case study on the comparison of the two regulations show that there is an increase in the basic earthquake force by 1.02%. Meanwhile, in relation to drift ratio analysis, an increase of 1% on the X axis and 5.5% on the Y axis is obtained.